Enhancing energy storage capabilities of MoS2 nanoflowers through designing nanoarchitecture by controlling synthesis growth parameters. (February 2023) - Rani, Sonam; Tanwar, Manushree; Sharma, Meenu; Bansal, Love; Kumar, Rajesh; Bhatia, Ravi; Ivaturi, Sameera
Abstract: Among transition metal dichalcogenides, molybdenum disulfide (MoS2 ) is considered as the most cost-effective electrode material for energy storage applications such as supercapacitors and supercapatteries. The layered morphology, intrinsic high surface area and edge sites favour the enhanced energy storage performance of MoS2 nanostructures. Low-cost, solution based hydrothermal synthesis has been considered as the most attractive route for the growth of exotic MoS2 nanostructures for their potential applications in energy storage devices. Yet, the performance of an electrode in a supercapacitor is related to the structural aspects such as morphology, crystallinity and phase which in turn can be tailored suitably by altering the synthesis conditions. Here in, we report a detailed study on the role of synthesis parameters such as reaction time, temperature and precursor amount on the capacitive performance of MoS2 nanoflowers by one-step hydrothermal synthesis. The morphological and structural analysis of the samples were carried out using various characterization techniques including electron microscopy, X-ray diffraction, Raman, UV–Visible and X-ray photoelectron spectroscopy. Tuning the inter-layer spacing by altering the synthesis conditions of MoS2 nanoflowers resulted in the enhanced charge storage performance. A superior value of specific capacitance ~215 F/g with high power density of ~1 kW/kg with an energy density of ~30 Wh/kg, respectively, have been achieved for bare MoS2 nanoflowers, simply by tailoring the synthesis conditions. Graphical abstract: Unlabelled Image Highlights: Probing the role of growth parameters on the electrochemical performance of MoS2 Impact of defects on the specific capacitance of MoS2 nanoflowers was studied. Inter-layer space engineering to enhance the electrochemical performance of MoS2 Studied the role of EDLC and pseudocapacitive behaviour on the capacitance of MoS2